Immunostimulants: Towards Temporary Prevention of Diseases in Marine Fish - Galindo-Villegas, J.; Hosokawa, H. (Facultad de Ciencias Biologicas, 2019)
Due over the last years, marine aquaculture has grown into a very significant industry in many parts of theworld, and in most developed countries marine fish are farmed intensively under conditions of highpopulation density, infectious diseases pose a constant and highly cost threat to successful animalhusbandry. Antibiotics provide a useful means of helping to control many bacterial diseases but there aremany problems associated with the development of antibiotic resistance and recurrent outbreaksnecessitating further, costly, treatments. Immunostimulants especially when administered through the diethave been perceived as potentially playing an important role in aquaculture. Efficiencies and strategic useof immunostimulation methods are presented and dose-effects between species analyzed. In addition,updated reviews of effects reported by several authors with nutritional and non-nutritional factors testedas immunostimulants in marine fish are presented; and those recent findings on the wide range of humoraland cellular innate immune responses affected by immunostimulation summarized. We conclude thatactual knowledge of potential immunostimulants is still obscure in several aspects, especially in thoserelated to pathways and mechanisms in which such substances can reach their specific cells targets.Nevertheless, immunostimulants as diet supplement, especially those of non-nutritional origin, should begood choice to induce a brief disease resistance enhancement in marine fish; although, methods andselected assess immune responses should be standardized between researchers in the aim ofunderstanding better the complexity of disease resistance and immune function to make easier thedevelopment of these therapies until the production scale and not just as mare laboratory trials.